A sequential finite element model updating routine to identify creep parameters for filament wound composite cylinders in aggressive environments. (February 2023) - Almeida, José Humberto S.; Lisbôa, Tales V.; Spickenheuer, Axel; St-Pierre, Luc
Graphical abstract: Highlights: Identification of primary and secondary creep parameters. Heuristic algorithm to avoid local minima. Gradient–based algorithm to ensure finding the global minimum. Fine-tuning of elastic constants for cylinders in harsh environments. Abstract: In this paper, a Finite Element Model Updating (FEMU) procedure is developed to find the best creep parameters for filament-wound cylinders under radial compression in harsh environmental conditions. Three winding angles are considered, each under three different hygrothermal conditions. The two–stage creep model captures i) primary creep through a time–hardening approach whilst ii) secondary creep is captured by Norton's law. Given the high number of parameters in this two–stage creep model and the complexity of determining them experimentally, the FEMU routine utilises an optimisation scheme that sequentially couples a Genetic Algorithm (GA) with a gradient-based (GB) Levenberq-Marquardt Algorithm (LMA) to find all required creep input parameters to feed the model that best simulates experimental results. This framework finds the global optimum through an initial screening of the optimum area within the design space with GA, clearing the path to allow the GB algorithm to find the global optimum, substantially reducing the chance or even avoiding falling in local minima. The global search is driven by experimental data of cylinders loaded in radial compression under aggressive environments. The numerical results show excellent agreement with experimental results with reasonably low computational efforts.